Soil carbon losses by sheet erosion: a potentially critical contribution to the global carbon cycle. Issue 13 (19th June 2015) - Müller‐Nedebock, Daniel; Chaplot, Vincent
Abstract Despite soil erosion through water being a ubiquitous process and its environmental consequences being well understood, its effects upon the global carbon cycle still remain largely uncertain. How much soil organic carbon (SOC) is removed each year from soils by sheet wash, an important if not the most efficient mechanism of detachment and transport of surficial soil material? What are the main environnemental controls worldwide? These are important questions which largely remain unanswered. Empirical data from 240 runoff plots studied over entire rainy seasons from different regions of the world were analysed to estimate particulate organic carbon (POC) losses (POCL), and POC enrichment in the sediments compared to the bulk soil (ER), which can be used as a proxy of the fate of the eroded POC. The median POCL was 9.9 g C m‐2 y‐1 with highest values observed for semi‐arid soils (POCL = 10.8 g C m‐2 y‐1), followed by tropical soils (POCL = 6.4 g C m‐2 y‐1) and temperate soils (POCL = 1.7 g C m‐2 y‐1). Considering the mean POCL of 27.2 g C m‐2 y‐1, the total amount of SOC displaced annually by sheet erosion from its source would be 1.32 ± 0.20 Gt C, i.e. 14.6% of the net annual fossil fuel induced C emissions of 9 Gt C. Because of low sediment enrichment in POC, erosion‐induced CO2 emissions are likely to be limited in clayey environments while POC burial within hillslopes is likely to constitute an important carbon sink. In contrast, most of the POC displaced from sandy soils is likely to be emitted to the atmosphere. These results underpin the major role sheet wash plays in the displacement of SOC from its source and in the fate of the eroded SOC, with large variations across the different pedo‐climatic regions of the world. Copyright © 2015 John Wiley & Sons, Ltd.